Carnegie Supernova Project I and II: Measurements of H 0 Using Cepheid, Tip of the Red Giant Branch, and Surface Brightness Fluctuation Distance Calibration to Type Ia Supernovae - Uddin, Syed A. (2024)
We present an analysis of Type Ia supernovae (SNe Ia) from the Carnegie Supernova Project I and II and extend the Hubble diagram from optical to near-infrared wavelengths (uBgVriYJH). We calculate the Hubble constant, H0, using various distance calibrators: Cepheids, the tip of the red giant branch (TRGB), and surface brightness fluctuations (SBFs). Combining all methods of calibration, we derive H0 = 71.76 ± 0.58 (stat) ± 1.19 (sys) km s−1 Mpc−1 from the B band and H0 = 73.22 ± 0.68 (stat) ± 1.28 (sys) km s−1 Mpc−1 from the H band. By assigning equal weight to the Cepheid, TRGB, and SBF calibrators, we derive the systematic errors required for consistency in the first rung of the distance ladder, resulting in a systematic error of 1.2 ∼ 1.3 km s−1 Mpc−1 in H0. As a result, relative to the statistics-only uncertainty, the tension between the late-time H0 we derive by combining the various distance calibrators and the early-time H0 from the cosmic microwave background is reduced. The highest precision in SN Ia luminosity is found in the Y band (0.12 ± 0.01 mag), as defined by the intrinsic scatter (σint). We revisit SN Ia Hubble residual-host mass correlations and recover previous results that these correlations do not change significantly between the optical and near-infrared wavelengths. Finally, SNe Ia that explode beyond 10 kpc from their host centers exhibit smaller dispersion in their luminosity, confirming our earlier findings. A reduced effect of dust in the outskirts of hosts may be responsible for this effect.